Outcome of ultrasound guided foam sclerotherapy (UGFS) treatment for varicose veins: A four years retrospective study at a tertiary care hospital in north India - Sanjay Singh; Akhilesh Kumar Maurya; Mayurika Singh; Vikas Sachdeva (International Journal of Medical Research and Review, 2016)
Objective:The purpose of this study was to determine the outcome and rate of recurrence for varicose veins treated with ultrasound-guided foam sclerotherapy (UGFS).Methods:Data was collected from hospital records. Patients treated with UGFS for superficial venous insufficiency were included in the study. Total 361 legs in 241 patients, out of which 121 patients with unilateral limbs and 120 patients with bilateral limbs were found to be treated by this method.Results:Out of these 361 legs great saphenous vein (GSV) varicosity was found in 88 legs, short saphenous vein (SSV) in 76, GSV & SSV both in 63, others 134. 264 legs with primary varicosity while 97 were with recurrent. In 294 legs clinical CEAP was 2-3 while in 67 legs it was 4-6. Saphenofemoral junction (SFJ) incompetence was found 60 legs, saphenopopliteal junction (SPJ) incompetence in 68, only perforator’s incompetence was in 56, SFJ with perforator’s incompetence 61, SPJ with perforator’s 29 and no incompetence was noted in 87 legs.Outcome at 6 months was 96.23% while treatment failure and recurrences were noted in 2.77 % of legs. Complications which were noted at 1 week were superficial skin necrosis in 3.04%, pain at injection sites in 15.23%, superficial thrombophlebitis in 16.62%, bruising in 12.18%, skin staining in 11.08%, superficial vein thrombosis (SVT) in 9.97% while no DVT was noted in any of the treated legs.Conclusion:On conclusion it was found that UGFS is a popular office based treatment modality, safe, effective, easy and improvement in venous signs and symptoms. Even on recurrence patients easily accepts retreatment with this method. Furthermore it is associated with lesser pain, anesthesia requirements; time off work and driving gives it additional advantages